Self-image and the image of the Other in foreign language teaching on the example of a GFL lesson in Poland - Mihułka, Krystyna (Glottodidactica, 2022)
This article aims at providing an answer to the question of whether, and if so to what extent (intensive) German language learning and exploring German culture leads to a positive change in the image of Germany and Germans in Poland. The article opens with theoretical considerations on the Us–Them dichotomy, the essential components of self-image and the image of the Other, as well as the interpenetration of the self and otherness. In turn, the empirical part of the article, which is directly related to the theoretical one, is devoted to the analysis of the results of a qualitative study conducted among Polish students of German Philology. The results of the analysis of the students’ utterances show that the exploration of German culture and the improvement of one’s German language proficiency at school and during German studies at university, as well as direct contact with the Germans have resulted in a positive change in the respondents’ attitudes towards Germany, Germans and the German language. The article ends with conclusions along with clearly outlined avenues for further research.